2022
DOI: 10.3390/ijerph19053135
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton Composition and Their Related Factors in Five Different Lakes in China: Implications for Lake Management

Abstract: In this paper, two trophic lakes: Lake Taihu and Lake Yanghe, and three alpine lakes: Lake Qinghai, Lake Keluke, and Lake Tuosu, were investigated to discover the connections between environmental factors and the phytoplankton community in lakes with differences in trophic levels and climatic conditions. Three seasonal data, including water quality and phytoplankton, were collected from the five lakes. The results demonstrated clear differences in water parameters and phytoplankton compositions in different la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Both abundance of bacteria and the taxonomic composition of the consortia can be correlated with pH, dissolved oxygen, or trophic state of the water ( Chopyk et al, 2018 ; Kiersztyn et al, 2019 ). The composition, structure and biomass of phytoplankton are highly correlated with nutrient concentration, pH, temperature and also salinity ( Reynolds, 1998 ; Jia et al, 2022 ). Interestingly, higher salinity was found to influence the germination of akinetes as well as the toxicity of N. spumigena , regardless of nutrient and temperature changes ( Silveira and Odebrecht, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both abundance of bacteria and the taxonomic composition of the consortia can be correlated with pH, dissolved oxygen, or trophic state of the water ( Chopyk et al, 2018 ; Kiersztyn et al, 2019 ). The composition, structure and biomass of phytoplankton are highly correlated with nutrient concentration, pH, temperature and also salinity ( Reynolds, 1998 ; Jia et al, 2022 ). Interestingly, higher salinity was found to influence the germination of akinetes as well as the toxicity of N. spumigena , regardless of nutrient and temperature changes ( Silveira and Odebrecht, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, overall, the model accuracy is satisfactory for both Z SD and C SPM with R 2 > 0.7. The Z SD and C SPM are highly correlated because the phytoplankton abundance in Qinghai Lake is not high [81], and the water clarity is mainly affected by the C SPM . The water clarity and C SPM estimated in this paper can only manifest partial optical and chemical characteristics of the water.…”
Section: Discussionmentioning
confidence: 99%
“…Lake Qinghai (36°32′–37°15′N; 99°36′–100°16′E) is located in northeastern ( Jia et al, 2022 ) Qinghai-Tibetan Plateau, and is the largest lake in China ( Figure 1 ). It covers an area of approximately 4,300 km 2 ( Tang et al, 2018 ), has a maximum depth of 30 m, and a mean surface elevation of 3,194 m. The lake is bordered by Qilian Mountains, AltynTagh Mountains, and the Kunlun Mountains ( Abirhire et al, 2015 ; Li et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…This in turn favors the growth and reproduction of nitrogen-fixing algae ( Dokulil and Teubner, 2000 ). In a high mountain lake, nutrient enrichment bioassays indicated that phytoplankton growth was severely limited by phosphorus due to overgrazing by pastoralists and ongoing climate change ( Ren et al, 2019 ; Jia et al, 2022 ). In contrast, nitrogen did not significantly impact phytoplankton growth, but excessive nitrogen is toxic to phytoplankton.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation